Factors influencing platelet apheresis yield and effects of donation among plateler aphersis donors - Muthalib, Nazri Abdul (2016)
The development in transfusion practice with discovery of advanced cell separators have defined platelet therapy in terms of quality and productivity. Previous studies have shown that transfusion of high yield platelet products could reduce the requirement of transfusion among thrombocytopenic patients The aim of this study was to investigate the factors that influence the platelet apheresis yield among apheresis donors by studying the donor variables and machine variables . Differences in donors peripheral count pre and post apheresis procedure were also studied. Correlation of serum ferritin level with platelet apheresis yield was also determined in this study. A prospective study was conducted from September 2015 to August 2016 at Hospital Universiti Sains Malaysia ( HUSM) , Kubang Kerian, Kelantan. Thirty five male subjects were recruited for this study Full blood count ( FBC ) and serum ferritin were taken prior to the donation. Post donation, another sample of FBC was taken. FBC and serum ferritin was run by Diagnostic Stago haematology analyser Sysmex XE 5000 and Bio-Architect respectively. FBC was analysed pre and post donation for haemoglobin level, haematocrit and platelet count. Other donors demographic data which included age, height, weight, frequency of donation and ABO blood group were taken from the donor apheresis registry book. Data regarding machine variables ( anticoagulation infusion rate, processing time and plasma volume collected ) were retrieved from the apheresis machine. The apheresis machine used in this study was Trima Accel cell separator. Height, pre donation platelet count and machine variables revealed significant positive correlations with platelet apheresis yield. There were also significant differences in donor peripheral counts pre and post apheresis procedure. Positive correlation of serum ferritin level with platelet yield was seen. No significant IDA was detected among the apheresis donors. In conclusion, some of the donors’ and all machine related variables showed significant relationship with platelet apheresis yield. There were also significant changes pre and post donation peripheral counts. Donors with high pre platelet count with adequate optimisation of machine variables can potentially produce a higher platelet apheresis yield collection.